Commis, artisans, ouvriers. Les métamorphoses du salariat dans l’Égypte du XIXe siècle - Pascale Ghazaleh (Université de Provence, 2004)
This article deals with the evolution of wage labour in Egypt during the first half of the 19th century, in light of the legal, military, economic, and administrative reforms instituted by Muhammad 'Alî (r. 1805-1848) . These reforms modified the system of venal office, whereby a sultan's subject could reach the status of servant by purchasing the right to military pay or a salary. The new institutions of the provincial state, rather than the sultan, were now the primary reference and source of livelihood for soldiers and administrators alike. Between 1840 and 1860 the replacement process was more or less completed and recruitment for State employment slowed down to a virtual, albeit temporary, halt. Thereafter, when the question of wage labour appeared as a public issue in the 1880s, it was dealt with primarily as a political matter - a metaphor for colonial occupation.